GERAKAN MASYARAKAT KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI DALAM MENDAPATKAN PERIZINAN PENGELOLAAN HUTAN DESA TAHUN 2009-2016 - Taufik Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Published Decree of the Minister of Forestry Number 217/Menhut-II/2007concerningthe Granting of Business License for Utilization of Forest Timber ForestProduct to PT. Lestari Unggul Makmur on 13 May 2007 covering 10,390 hectares inseven villages of Tebing Tinggi Timur Subdistrict after this natural forest which is theeyes of some communities become threatened because it will become the property ofcorporation that engaged in HTI.The theory used in this research is the concept of dynamics and social movementtheory. This research uses qualitative descriptive method, this research location inLukun Village, West Tohor River Village, Tohor River Village, Nipah Sendanu Village,Nipah Sendanu Village, Sendanu Darul Ihsan Village, Tanjung Sari Village and KepauBaru Village, Tebing Tinggi Timur Subdistrict, Meranti Island Regency. With the focusof research on the conflict betwween the seven villagers with PT. Lestari UnggulMakmur after the HTI licensing is issued in Tebing Tinggi Timur.Based on research conducted by the author in the field since 2009 PT. LestariUnggul Makmur (PT. LUM) in east Tebing Tinggi Sub-district of Meranti IslandRegency is granted a natural forest clearance license or Annual Working Pland (RKT)based on Directorate of Plantation Forest Development Decree No. 13/BPHT-3/2009on13 April 2009, 2,832 hectares with harvest targets of 262,873 M3 of natural timber,after which the community rejected the operation of PT. LUM in the community forestarea by conducting various protest actions to the Company, District Government,Provincial Goverment to the Central Covernment. The resistance movement begins withthe formation of the idea of resistance, collective actions such as demonstrations, selfimmolation,mouth sewing, statue-building actions and the efforts of these actions byusing the strategy of achieving the objectives of the resistance movement as united inthe action movement, depending on own strength, expansion of support andradicalization of movement. Conflict resolutionby the Goverment with mediation,negotiation, facilitation, conciliation, and yield resolution by revocationof HTI permitPT. LUM by the Ministry of Environment and Forestry SK444/Menlhk/Setjen/HPL.I/6/2016 and issued the Regulationof the Minister ofEnvironment and Forestry of the Republic of Indonesia NumberP.83/MENLHK/SETJEN/KUM.1/10/2016 Concerning Social Forestry as the basis ofthe Govement’s alignment with the people.Keywords : resistance movement, forest village, tebing tinggi timur.